2017
DOI: 10.4103/jpbs.jpbs_160_17
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of risk and complications associated with orthodontic therapeutic extraction

Abstract: Background:Extraction in orthodontics are carried out in the cases where there is space deficiency to align the teeth. The elective extraction of first or second premolars has been discussed in the literature for more than 50 years. In the 1940s and 1950s Nance, Dewel and Carey reviewed this as a useful option, and in the 1970s Logan and other leading orthodontists favoured the extraction as choice. It is not always the elective extraction of premolar is a smooth drive for the surgeon as well as to patient. So… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
1
0
0
Order By: Relevance
“…They reported that physics forceps could be regarded as a reliable technique for safe and successful IR [ 15 ]. This study is also in line with the study by Shetty and John, who reported 12% root fractures in the conventional forceps group and 2% in the physics forceps group [ 19 ]. Furthermore, the lingual beak of physics forceps applies a steady and consistent tractional force along the root’s axis, and the bumper acts as the extraction fulcrum.…”
Section: Discussionsupporting
confidence: 92%
“…They reported that physics forceps could be regarded as a reliable technique for safe and successful IR [ 15 ]. This study is also in line with the study by Shetty and John, who reported 12% root fractures in the conventional forceps group and 2% in the physics forceps group [ 19 ]. Furthermore, the lingual beak of physics forceps applies a steady and consistent tractional force along the root’s axis, and the bumper acts as the extraction fulcrum.…”
Section: Discussionsupporting
confidence: 92%